Investigating the causal association between branched-chain amino acids and Alzheimer's disease: A bidirectional Mendelian randomized study - Qian, Xiao-hang; Liu, Xiao-li; Zhang, Bin; Lin, Yuan; Xu, Jian-hua; Ding, Gang-yu; Tang, Hui-dong (Frontiers in Nutrition, 2023)
Background There are many metabolic pathway abnormalities in Alzheimer's disease (AD). Several studies have linked branched-chain amino acid (BCAA) metabolism disorders with AD but have not obtained consistent results. The purpose of this study is to explore the causal association between BCAA concentration and the risk of AD. Methods A bidirectional Mendelian randomized (MR) study was applied to explore the causal effect between BCAA level and the risk of AD. Genetic instrumental variables from the genome-wide association study (GWAS) of serum BCAA levels [total BCAAs (115,047 participants), valine (115,048 participants), leucine (115,074 participants), and isoleucine (115,075 participants)] from the UK Biobank and AD (21,982 AD cases and 41,944 controls) from the International Genomics of Alzheimer's Project were applied to explore the causal effect through the inverse variance-weighted (IVW) method, MR-Egger, and weighted median, accompanied by multiple pluripotency and heterogeneity tests. Results The forward MR analysis showed that there was no causal effect of total BCAAs (OR: 1.067, 95% CI: 0.838–1.358; p = 0.838), valine (OR: 1.106, 95% CI: 0.917–1.333; p = 0.292), leucine (OR: 1.096, 95% CI: 0.861–1.396; p = 0.659), and isoleucine (OR: 1.457, 95% CI: 1.024–2.742; p = 0.037) levels on the risk of AD. The reverse analysis showed that AD was related to reduced levels of total BCAAs (OR: 0.979, 95% CI: 0.989–0.990; p < 0.001), valine (OR: 0.977, 95% CI: 0.963–0.991; p = 0.001), leucine (OR: 0.983, 95% CI: 0.973–0.994; p = 0.002), and isoleucine (OR: 0.982, 95% CI: 0.971–0.992; p = 0.001). Conclusion We provide robust evidence that AD was associated with a decreased level of BCAAs, which can serve as a marker for early diagnosis of AD.